Factors Contributing to Deficit Spending in Indonesia - Walyoto, Sri; Soebagiyo, Daryono; Hapsoro, Ahmad Luthfi Ridho (Shirkah: Journal of Economics and Business, 2021)
The issues concerning deficit spending have been a major concern in macroeconomic policies. Each country has a different method to solve the problems, including by devising appropriate deficit spending policies. This study investigates the effect of deficit spending in Indonesia. The effect of deficit management is seen from the sources to finance budget deficit, the efforts that are made, and the ability to contribute to the economy. Another research objective is to identify the magnitude of the effect of deficit spending and its effect on the national economy. This study attempts to explain that the applied model is able to determine the factors that contribute to deficit spending in Indonesia. The findings of this study reveal that both in the short- and long-run, external debts have a positive and significant effect on deficit spending. On the contrary, the economic growth and inflation rate have no significant effect on deficit spending.